Singrar rios, morar em cavernas e furar jatoká: ressignificações culturais, socioespaciais e espaços de aprendizagens da família Avá-Canoeiro do Rio Tocantins - Silva, Lorranne Gomes da (2016)
The present investigation analyzes how different times and spaces in which the Avá-Canoeiro indigenous family from river Tocantins has been living triggered sociocultural and spatial resignifications. The investigation specially relies on three time-space contexts: “sailing rivers”, which refers to river displacements and pre-massacre tribe time in the mata do café; “cave dwelling”, which refers to the period when there were scapes throughout the Cerrado in the North of Goiás in the post-massacre and “piercing Jatóka”, which refers to memory and a material culture-related process update in the indigenous land. It was possible to understand that the different moments lived and experienced by each Avá-Canoeiro individual and/or by the group in a given time-space pressupose reconfigurations in terms of life styles and sociocultural relationships caused by the displacements and by new life adaptations and that, by respecting and understanding the Avá-Canoeiro’s sociospacial organization and their learning environments, education and culture, it is feasible to collaborate so as to strengthen their identity. . Thus, living/existing, above all, scaping, generated spatial practices (translated by spatial resignification, relationship networks and survival strategies) and a specific family mode in terms of memory, education and culture. Reduced, forced to abandon their customs and cultural practices, they have started to develop survival strategies. Reduced, forced to abandon their customs and cultural practices, they have been developing survival strategies. The dissertation is organized in six chapters. Regarding methodology, there was participatory observation, conversation rounds and interviews. The theoretical background resorts fundamentally to Rodrigues (2008, 2012, 2013, 2015); Borges (2006); Granado (2005); Silva (2005) and Pedroso (1994).